Factors associated with the Single Leg Squat test in female soccer players: a cross-sectional study - John Ressman; Philip von Rosen; Wilhelmus Johannes Andreas Grooten; Eva Rasmussen-Barr (BMC, 2024)
Abstract Background The Single Leg Squat (SLS) test is widely used in the clinical setting to examine and evaluate rehabilitation goals. It is simple to perform and is proposed to have biomechanical and neuromuscular similarities to athletic movements. The aim of the present study was to investigate whether demographics, previous injuries, and biomechanical and psychosocial factors are associated with the outcome of the SLS, assessed as a total score for all segments and as a separate knee segment in elite and sub-elite female soccer players. Methods We conducted a cross-sectional study involving 254 female soccer players (22 yrs; SD ± 4, height 1.69 m; SD ± 0.1, weight 64 kg; SD ± 6) from divisions 1-3 of the Swedish Soccer League. During the preseason, we assessed the participants using the SLS and tested their hip strength and ankle mobility. Demographics, previous injury, sleep quality, fear of movement, anxiety, and perceived stress were assessed with questionnaires. Logistic regression models were built to analyse the association between the outcome of the SLS and the independent variables for the dominant and non-dominant leg. Results Significantly more participants failed the SLS on the dominant leg compared with the non-dominant leg (p < 0.001). The outcome of the SLS associated with various biopsychosocial factors depending on if the dominant or non-dominant leg was tested. The total score associated with hip strength for the dominant (OR 0.99, 95% CI 0.98-0.99, p = 0.04) and the non-dominant leg (OR 0.99, 95% CI 0.97-0.99, p = 0.03). The knee segment associated with division level for the dominant (div 2; OR 2.34, 95% CI 1.01-5.12, p = 0.033. div 3; OR 3.07, 95% CI 1.61-5.85, p = 0.001) and non-dominant leg (div 2; OR 3.30, 95% CI 1.33-8.00, p = 0.01. div 3; OR 3.05, 95% CI 1.44-6.43, p = 0.003). Conclusions This study identified that leg dominance, division level, hip strength, and psychosocial factors were associated with the outcome of the SLS when assessed as a total score and as a separate knee segment. This indicates that clinicians need to understand that movement control is associated with factors from several domains. Whether these factors and, the results of the SLS are related to injury need to be studied prospectively. Trial registration Clinical Trials Gov, date of registration 2022-03-01. Clinical trials identifier: NCT05289284A.